Visualisation of Flow at the Headland-generated Recirculation Zone - Tang, Fu Ee (Universiti Teknologi Malaysia, 2009)
Experimental investigations were carried out in the Manchester Tidal flow Facility (MTF) to study the recirculation zone generated by flow past a headland in shallow steady flow. The experiments were performed in a flume with a rough, sloped beach. Fluorescent dye was released at specific points on a grid located in the generated recirculation zone. The Planar laser-induced fluorescence (PLIF) technique was used for flow visualisation. Residual dye decay profiles were also produced from raw PLIF images to study the flushing characteristics. Compared to discharge at other locations, trapping of released dye here is significant, and a relatively long time is needed to flush the residual dye. The decay profiles agreed with the observations from flow visualisation. The recirculatory flow acted to retain and increase the residual dye, and eventually flushed it into the free stream. A dead zone, where flow is almost stagnant and severe trapping occurs, has been identified about one width of the headland away, near the shore. This has serious implications towards the water quality in such areas in real life situations.